Effect of Strain-Dependent Hydraulic Conductivity of Coal Rock on Groundwater Inrush in Mining - Haifeng Lu; Nan Shan; You-Kuan Zhang; Xiuyu Liang (Geofluids)
Hydraulic conductivity is an important parameter for predicting groundwater inrush in coal mining worksites. Hydraulic conductivity varies with deformation and failure of rocks induced by mining. Understanding the evolution pattern of hydraulic conductivity during mining is important for accurately predicting groundwater inrush. In this study, variations of hydraulic conductivity of rock samples during rock deformation and failure were measured using the triaxial servo rock mechanic test in a laboratory. The exponential formula of hydraulic conductivity-volume strain was proposed based on the experimental data. The finite-difference numerical model FLAC3D was modified by replacing constant hydraulic conductivity with the strain-dependent hydraulic conductivity. The coupled water flow and rock deformation and failure were simulated using the modified model. The results indicate that in the early time, the rocks undergo elastic compression with increasing rock strain, resulting in a decrease in hydraulic conductivity; then, the microcracks and fissures appear in the rock after it yields results in a sudden jump in hydraulic conductivity; in the later time, the hydraulic conductivity decreases gradually again owing to the microcracks and fissures that were compacted. The conductivity exponentially decreases with the volumetric strain during the periods of both elastic compression and postyielding. The simulated stress-strain curves using the modified model agree with the triaxial tests. The modified model was applied to the groundwater inrush of a coal mining worksite in China. The simulated water inflow agrees well with the observed data. The original model significantly underestimates the water inflow owing to it to neglect the variations of the hydraulic conductivity induced by mining.